GROSS AND MICROSCOPIC STRUCTURE OF THE CAROTID BODY IN THE ROCKY PIGEON (COLUMBA LIVIA). - S. Al-Samarrae, N.; K. Arak, J.; 0. Rabie, F. (The Iraqi Journal of Veterinary Medicine, 1994)
Topographically, the carotid body in rocky pigeon has a silvery-white in in colour and showed different localization. It located on or in the vicinity of the carotid and lateral to the caudal thyroid arteries. It was located in close apposition to the parathyroid glands. Histologically, the parenchyma of carotid body in rock pigeon was consisted of chief cells and sustentacular cells. These epothelioid tissue was interspersed by connective tissue with some sinuses and relatively number of capillaries. Nerve fibers were Found also in the connective tissue between the parenchymal cells.